Insulin resistance after a 3-day fast is associated with an increased capacity of skeletal muscle to oxidize lipids - Blackwood, Sarah J.; Horwath, Oscar; Moberg, Marcus; Pontén, Marjan; Apró, William; Ekblom, Maria M.; Larsen, Filip J.; Katz, Abram (American journal of physiology: endocrinology and metabolism, 2023)
Whether lipid-mediated insulin resistance occurs as a result of an increased or decreased capacity of skeletal muscle to oxidize lipids has been debated. We show that a 3-day fast results in increases in circulating lipids and insulin resistance in subjects expressing a high or low proportion of type I muscle fibers. High expression of type I is associated with a higher capacity to oxidize lipids and a greater loss of insulin sensitivity after starvation. There is a debate on whether lipid-mediated insulin resistance derives from an increased or decreased capacity of muscle to oxidize fats. Here, we examine the involvement of muscle fiber composition in the metabolic responses to a 3-day fast (starvation, which results in increases in plasma lipids and insulin resistance) in two groups of healthy young subjects: 1), area occupied by type I fibers = 61.0 ± 11.8%; 2), type I area = 36.0 ± 4.9% ( P < 0.001). Muscle biopsies and intravenous glucose tolerance tests were performed after an overnight fast and after starvation. Biopsies were analyzed for muscle fiber composition and mitochondrial respiration. Indices of glucose tolerance and insulin sensitivity were determined. Glucose tolerance was similar in both groups after an overnight fast and deteriorated to a similar degree in both groups after starvation. In contrast, whole body insulin sensitivity decreased markedly after starvation in group 1 ( P < 0.01), whereas the decrease in group 2 was substantially smaller ( P = 0.06). Nonesterified fatty acids and β-hydroxybutyrate levels in plasma after an overnight fast were similar between groups and increased markedly and comparably in both groups after starvation, demonstrating similar degrees of lipid load. The capacity of permeabilized muscle fibers to oxidize lipids was significantly higher in group 1 versus 2, whereas there was no significant difference in pyruvate oxidation between groups. The data demonstrate that loss of whole body insulin sensitivity after short-term starvation is a function of muscle fiber composition and is associated with an elevated rather than a diminished capacity of muscle to oxidize lipids. NEW & NOTEWORTHY Whether lipid-mediated insulin resistance occurs as a result of an increased or decreased capacity of skeletal muscle to oxidize lipids has been debated. We show that a 3-day fast results in increases in circulating lipids and insulin resistance in subjects expressing a high or low proportion of type I muscle fibers. High expression of type I is associated with a higher capacity to oxidize lipids and a greater loss of insulin sensitivity after starvation.